Plant species identity and mycorrhizal type explain the root-associated fungal pathogen community assembly of seedlings based on functional traits in a subtropical forest - Li, Yongning; Xie, Yan; Liu, Zhengjiao; Shi, Liuqing; Liu, Xubing; Liang, Minxia; Yu, Shixiao (Frontiers in Plant Science, 2023)
As a crucial factor in determining ecosystem functioning, interaction between plants and soil-borne fungal pathogens deserves considerable attention. However, little attention has been paid into the determinants of root-associated fungal pathogens in subtropical seedlings, especially the influence of different mycorrhizal plants. Using high-throughput sequencing techniques, we analyzed the root-associated fungal pathogen community for 19 subtropical forest species, including 10 ectomycorrhizal plants and 9 arbuscular mycorrhizal plants. We identified the roles of different factors in determining the root-associated fungal pathogen community.Further, we identified the community assembly process at species and mycorrhizal level and managed to reveal the drivers underlying the community assembly. We found that plant species identity, plant habitat, and plant mycorrhizal type accounted for the variations in fungal pathogen community composition, with species identity and mycorrhizal type showing dominant effects. The relative importance of different community assembly processes, mainly, homogeneous selection and drift, varied with plant species identity. Interestingly, functional traits associated with acquisitive resource-use strategy tended to promote the relative importance of homogeneous selection, while traits associated with conservative resource-use strategy showed converse effect. Drift showed the opposite relationships with functional traits compared with homogeneous selection. Notably, the relative importance of different community assembly processes was not structured by plant phylogeny. Drift was 2 stronger in the pathogen community for ectomycorrhizal plants with more conservative traits, suggesting the predominant role of stochastic gain and loss in the community assembly. Our work demonstrates the determinants of root-associated fungal pathogens, addressing the important roles of plant species identity and plant mycorrhizal type. Furthermore, we explored the community assembly mechanisms of root-associated pathogens and stressed the determinant roles of functional traits, especially leaf phosphorus content (LP), root nitrogen content (RN) and root tissue density (RTD), at species and mycorrhizal type levels, offering new perspectives on the microbial dynamics underlying ecosystem functioning.